Analysis of The Influence of Situational Leadership Style, Work Environment and Work Discipline on Work Motivation and Performance of GSE PT Employees Gapura Surabaya - Evitaningrum, Evitaningrum; Sardjono, Sigit (Jurnal Riset Ekonomi, Manajemen, dan Bisnis, 2024)
This study aims to examine and analyze the influence of situational leadership, work environment, work discipline on work motivation and the performance of GSE employees of PT. Gapura Surabaya. Data collection was carried out through distributing questionnaires to 112 employees of PT Gapura Surabaya's GSE Unit. Data analysis in this study uses SPSS and AMOS. The sampling technique used is saturated sampling method and data testing techniques used in this study include validity test with factor analysis, reliability testing with Alpha Cronbach. SEM (Structural Equation Modeling) Test, to test and prove the research hypothesis. The analysis shows that situational leadership has a significant influence on employee motivation. Situational leadership has no significant effect on employee performance. The work environment has a significant influence on work motivation. The work environment has a significant effect on employee performance. Work discipline has a significant influence on work motivation. Work discipline has a significant influence on employee performance. Work motivation has a significant influence on employee performance.